This is philosophy of religion an introduction - Manson, Neil A. 1967- (Hoboken, NJ Wiley Blackwell, 2021)
"This book was written with my University of Mississippi "Philosophy of Religion" students in mind. Many of them have no prior experience with philosophy. That is why Chapter One begins with a crash course in philosophy, with an emphasis on the basic concepts in logic, metaphysics, and epistemology. While not all students may need to cover that material, quite a few will. And for the rest, a refresher never hurts. I am sure this applies to many "Philosophy of Religion" courses taught elsewhere. With that in mind, instructors are advised to begin with Chapter One. The subsequent chapters have been arranged in sequence, with each chapter building on the prior ones. However, the chapters are not that tightly bound, so instructors could cover the chapters out of sequence without much disruption. Key terms are underlined. Sometimes the key terms also occur with an associated hyperlink. Other terms have a hyperlink without a corresponding key term. In the print the hyperlink is included as a footnote, in the ebooks the term is hyperlinked [Production - check the ebooks will have hyperlinbks - amend wording here if not]. In general, the hyperlinks follow a pattern. First, key terms are often linked to entries in online academic encyclopedias - either The Stanford Encyclopedia of Philosophy, The Internet Encyclopedia of Philosophy, or The Encyclopedia Britannica. [Students are recommended also to consult The Encyclopedia of Philosophy (1967), edited by Paul Edwards; it is still an excellent resource and has entries corresponding to many key terms. Almost every university library has a copy.] Second, named individuals are sometimes linked to an encyclopedia entry. In both sorts of cases, the URL is provided in an endnote at the end of each chapter. No other description of the contents of the web page will be given. In most other cases, a short description of the contents of the web page is provided in the endnote. Each chapter includes an annotated bibliography for more advanced material. Helpful material is also available on the website for this book. This material includes a glossary, a sample syllabus (with recommended readings), study questions, and a test bank, among other features"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Religion -- Philosophy -- Textbooks